ADMINISTRATIVE ACTIVITY OF LAW ENFORCEMENT AGENCIES OF UKRAINE (THE PROCURACY OF UKRAINE AND THE SFS OF UKRAINE) - Hrechaniuk, Serhii; Puzyrna, Natalia; Tereshchuk, Galina; Hrechaniuk, Rorsolana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Prosecution authorities in Ukraine perform four basic functions fixed by the Constitution of Ukraine. Constitution of Ukraine provides that on the procuracy of Ukraine are laid the following powers: 1) state accusation in court; 2) representation of interests of citizens or state in court in cases determined by law; 3) supervision over observance of laws by bodies conducting operational and search activity, inquiry and pretrial investigation